The High performance of nanocrystalline CVD diamond coated hip joints in wear simulator test. (September 2015) - Maru, M.M.; Amaral, M.; Rodrigues, S.P.; Santos, R.; Gouvea, C.P.; Archanjo, B.S.; Trommer, R.M.; Oliveira, F.J.; Silva, R.F.; Achete, C.A.
Abstract: The superior biotribological performance of nanocrystalline diamond (NCD) coatings grown by a chemical vapor deposition (CVD) method was already shown to demonstrate high wear resistance in ball on plate experiments under physiological liquid lubrication. However, tests with a close-to-real approach were missing and this constitutes the aim of the present work. Hip joint wear simulator tests were performed with cups and heads made of silicon nitride coated with NCD of ~10 μm in thickness. Five million testing cycles (Mc) were run, which represent nearly five years of hip joint implant activity in a patient. For the wear analysis, gravimetry, profilometry, scanning electron microscopy and Raman spectroscopy techniques were used. After 0.5 Mc of wear test, truncation of the protruded regions of the NCD film happened as a result of a fine-scale abrasive wear mechanism, evolving to extensive plateau regions and highly polished surface condition (Ra<10 nm). Such surface modification took place without any catastrophic features as cracking, grain pullouts or delamination of the coatings. A steady state volumetric wear rate of 0.02 mm 3 /Mc, equivalent to a linear wear of 0.27 μm/Mc favorably compares with the best performance reported in the literature for the fourth generation alumina ceramic (0.05 mm 3 /Mc). Also, squeaking, quite common phenomenon in hard-on-hard systems, was absent in the present all-NCD system. Graphical abstract: Highlights: Wear behavior of nanocrystalline diamond coated silicon nitride hip joints is shown. Five million cycles of lab simulated wear test results are presented. Very small volume wear of 0.02 mm 3 /Mc. Very small linear wear rate of 0.27 mm/Mc. Truncation of the protruded regions takes place by fine-scale abrasion mechanism.